Positioning policies of the Argentine Hydrocarbons Sector After the Partial Nationalization of YPF (2012-2015) - Pérez-Roig, Diego (Sociedad y Economía, 2021)
This article analyzes the policies designed and implemented in Argentina, between 2012 and 2015, with the purpose of promoting the obtaining of hydrocarbons from “unconventional” reservoirs. In 2012, the “Hydrocarbon Sovereignty” Law provided for the recovery of state control of Yacimientos Petrolíferos Fiscales (YPF) and turned those resources into strategic objectives of the energy policy. This implied the subsequent adoption of a wide range of measures aimed at attracting foreign investors. From the perspective of the internationalization of capital and the State, this set of measures is shown as “positioning policies” that must face different limits and contradictions associated with the volatility of the world market, the local dynamics of accumulation and the production of consensus. To this end, a mixed methodological strategy was employed, based on the triangulation of methods and techniques of information collection and data analysis.